2009 IEEE International Symposium on Circuits and Systems 2009
DOI: 10.1109/iscas.2009.5117733
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic synthesis methodology implemented on the sine function

Abstract: Abstract-This paper introduces a parabolic synthesis methodology for implementation of approximations of unary functions like trigonometric functions and logarithms, which are specialized for efficient hardware mapped VLSI design. The advantages with the methodology are, short critical path, fast computation and high throughput enabled by a high degree of architectural parallelism. The feasibility of the methodology is shown by developing an approximation of the sine function for implementation in hardware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…That is, the choice of function is given by the (small) table of coefficients. In earlier papers, it was shown that Parabolic Synthesis can be used with good results on several functions (e.g., the sine function [9] and the exponential function [11]). Since the Harmonized version of Parabolic Synthesis, presented in the current paper, can be applied to any functions (even without the limitations of earlier methods) it can be concluded that it is an efficient method for a wide class of functions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the choice of function is given by the (small) table of coefficients. In earlier papers, it was shown that Parabolic Synthesis can be used with good results on several functions (e.g., the sine function [9] and the exponential function [11]). Since the Harmonized version of Parabolic Synthesis, presented in the current paper, can be applied to any functions (even without the limitations of earlier methods) it can be concluded that it is an efficient method for a wide class of functions.…”
Section: Resultsmentioning
confidence: 99%
“…This is computed by inserting the value of x for the starting point of the interval, x start,i , of the help function, f help (x), (4) as shown in (8) Eq. (8) does not apply on the start value of the first interval, which has to be calculated as the limit according to (9). Since the x 2 term in (9) goes faster towards 0 than the x term, it can be excluded when calculating the limit, as shown in (9).…”
Section: The Second Sub-functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this paper will not consider truncation and rounding since it will reduce the precision. The most costly computation is thus the squaring [6][7] [8] in the Squared Euclidean Distance unit.…”
Section: Hardware Considerationsmentioning
confidence: 99%
“…It uses the product of series of sub-functions to approximate the original reciprocal function, and it indicates performance improvement over CORDIC and Newton-Raphson method [9]. Parabolic synthesis method has shown a wide application in arbitrary function, e.g., sine and cosine function [10], [11], logarithmic and exponential function [12], and roots, inverse and inverse roots function [13]. To further release the hardware burden and improve the computing precision of reciprocal, harmonized parabolic synthesis (HPS) [14] and non-linear interpolation [15] have been proposed recently.…”
Section: Introductionmentioning
confidence: 99%